Pengaruh Kejelasan Sasaran Anggaran, Kompetensi Aparatur Desa, dan Kepemimpinan Pada Akuntabilitas Pengelolaan Dana Desa di Kecamatan Gianyar - Pramayoga, Ida Bagus; Ramantha, I Wayan (E-Jurnal Akuntansi; Vol 30 No 1 (2020), 2020)
Underlying this research are findings related to misuse and management of village funds in Gianyar District. This study aims to determine the effect of clarity of budget targets, competence of village officials, and leadership on accountability of village fund management in Gianyar District. The sample collection method used was a questionnaire and analyzed using Multiple Linear Regression analysis. Based on the results of the analysis conducted, it can be concluded that the clarity of the budget targets, the competence of the village apparatus, and leadership has a positive effect on the accountability of village fund management, which means that the clarity of the budget targets, the competence of the village apparatus, and the leadership of the related leaders are better. accountability of the management of village funds in the District of Gianyar.